Ozonetherapy as a new antimicrobic strategy - Shahanenko R. (Науковий вісник ветеринарної медицини, 2020)
Development of antibiotic-resistant strains of microorganisms is a dangerous phenomenon, actively progressing every year. The uncontrolled use of antibiotics for animals, accumulation in products of animal origin ultimately poses a danger to human health. That is why a decrease in the use of antibiotics and searching alternatives of antibiotic is acute and relevant issues. Therefore, the aim of our research was to study the antimicrobial properties of ozone in relation to pathogens of purulent infection and to show the possibility of using ozone therapy as a potential method of antimicrobial therapy for animals. The materials for determining antimicrobial effect of ozone was 12 samples of purulent exudate in an amount of 2 ml, taken from dogs with purulent wounds before and after sanitation by ozonized 0.87% NaCl solution. Complexity course of wound process with purulent inflammation largely depends on from degree of microbial contamination of the wound and species composition of microorganisms. Therefore, an important aspect in our research was the study of the antimicrobial properties of ozone on its action of purulent exudate «in vitro» and «in vivo» and the determination of the bactericidal effect on microorganisms. The most stable and informative indicator of assessing nature of purulent-inflammatory process is the determination of total number of microorganisms in 1 ml of discharge from a purulent wound. The total microbial number was determined by the method of serial dilutions according to Pasteur. Serial ten-fold dilutions from 10-1 to 10-9 were prepared from purulent exudate in test tubes with sterile MPB (9 ml each). Species composition of microorganisms was determined by cultural and biochemical properties of cultivated microbial colonies, followed microscopy of smears from pure cultures stained using method of Gram. Samples of purulent exudate were subjected to microbiological examination before treatment, and after 30 minutes of washing by ozonized isotonic solution NaCl (ozone concentration of 7 mg/ml). A microbiological study of purulent exudate was also carried out, pre-treated with ozone at a concentration of 7 mg/ml «in vitro» in a test tube in an amount of 2 ml by passing it through exudate (sparging) at a flow rate of 0.5 L/min and a processing time of 10 min. Samples were examined immediately after sampling and sparging. "Microbial landscapes" of purulent wounds were presented by associations of Staph. aureus, Str. faecalis, E. coli. Microbial seeding of purulent exudate for treatment ranged from 6.6 • 10-10 to 3.7 • 10-8 CFU/ml, however, after 10 min of bubbling «in vitro» at an ozone concentration of 7 mg/ml, the degree of microbial seeding of samples did not exceed 10-4 CFU/ml and ranged from 3.1 • 10-4 to 2.3• 10-3 CFU/ml. As shown by the results of microbiological studies, the growth of microorganisms on a nutrient medium in bacteriological plates with purulent exudate samples treated with ozone with concentration of 7 mg/ml was already absent at 10-5 degrees of dilution, which indicates the pronounced antimicrobial properties of ozone. The study «in vivo»also indicates that even after a single use of an ozonized isotonic NaCl solution at an ozone concentration of 7 mg/ml, it completely prevents the growth of Staph. aureus, Str. faecalis, E. coli. and causes 100% death mentioned associations of microorganisms. The results of microbiological studies are confirmed by clinical data. So, on the third day of treatment, the animals in the lesion zone had a small amount of wound exudate, and the microbial number of the latter was 1.4 • 10-4 − 3.1 • 10-³ CFU/ml, below the critical level of contamination and in most cases not leads to the progression of a purulent-inflammatory process. Ozone destroys all types of bacteria, viruses, fungi and protozoa. At the same time, ozone at a concentration of 7 mg/ ml does not have an irritating effect on body tissues, therefore, ozone therapy can be considered as an additional or alternative therapy of bacterial infection.